Brain activity during visuospatial working memory in congenital adrenal hyperplasia. (February 2023) - van't Westeinde, Annelies; Zimmermann, Marius; Messina, Valeria; Karlsson, Leif; Padilla, Nelly; Lajic, Svetlana
Abstract: Context: Patients with congenital adrenal hyperplasia (CAH) require life-long replacement of cortisol. Problems with cognitive function, especially working memory, have previously been identified, but the long-term effects of this disease on brain function are unknown. Objective: We investigate brain activity during working memory in CAH compared to controls. Design, setting, and participants: Twenty-nine individuals with CAH (17 females) and 40 healthy controls (24 females), 16–33 years, from a single research institute, underwent functional magnetic resonance imaging while doing a verbal and visuospatial working memory task. Results: Individuals with CAH responded faster on the verbal task. Although we found no differences in BOLD response over the whole group, there were significant interactions with sex: CAH males had increased activity in the bilateral lateral superior occipital cortex, left supramarginal and angular gyri, left precuneus, left posterior cingulate cortex and bilateral cerebellum during decoding of the visuospatial task, while females showed decreased activity in these regions. Conclusions: Long-term cortisol imbalances do not seem to have a major impact on the functional brain responses during working memory in CAH. However, activity of the left dorsal visual stream in particular might be affected depending on sex. As the task employed may have been relatively easy, larger studies using more complex tasks are needed to further investigate this.